2018
DOI: 10.1007/s10750-018-3780-z
|View full text |Cite
|
Sign up to set email alerts
|

The origin and future of an endangered crater lake endemic; phylogeography and ecology of Oreochromis hunteri and its invasive relatives

Abstract: Cichlids of the genus Oreochromis ("Tilapias") are intensively used in aquaculture around the world. In many cases when "Tilapia" were introduced for economic reasons to catchments that were home to other, often endemic, Oreochromis species, the loss of native species followed. Oreochromis hunteri is an endemic species of Crater Lake Chala on the slopes of Mount Kilimanjaro, and is part of a small species flock in the upper Pangani drainage system of Tanzania. We identified three native and three invasive Oreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Therefore, hybridization between introduced and native tilapia species can severely impact the unique genetic diversity of the latter affecting their adaptation capacity toward changing environmental conditions (Deines, Wittmann, Deines, & Lodge, 2016). Even though the exact consequences of introduced tilapia species in Tanzania to the local fauna are unknown, habitat loss and significant decline of population size have been recently documented for the endemic Oreochromis hunter in Lake Chala, in Kilimanjaro Tanzania due to introduced tilapia species (Moser, van Rijssel, Ngatunga, Mwaiko, & Seehausen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hybridization between introduced and native tilapia species can severely impact the unique genetic diversity of the latter affecting their adaptation capacity toward changing environmental conditions (Deines, Wittmann, Deines, & Lodge, 2016). Even though the exact consequences of introduced tilapia species in Tanzania to the local fauna are unknown, habitat loss and significant decline of population size have been recently documented for the endemic Oreochromis hunter in Lake Chala, in Kilimanjaro Tanzania due to introduced tilapia species (Moser, van Rijssel, Ngatunga, Mwaiko, & Seehausen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Output from an initial mapping using BWA (settings aln -t 2 -n 0.05, seeding disabled) was deduplicated using Samtools (Li et al, 2009), 'bandia', which was recently introduced into Lake Chala and has also been called O. sp. 'blue head' (Moser et al, 2018) or O. cf. korogwe (Dieleman et al, 2018).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Here, two invasive species are now abundant, Oreochromis cf. korogwe (Lowe-McConnell, 1955) and Coptodon rendalli (Boulenger, 1897), and there are signs of the endemic Chala tilapia Oreochromis hunteri Günther, 1889 being in decline (Moser et al, 2019). Through a longitudinal study of diet using stomach content analysis and stable isotope ratios of carbon (d 13 C) and nitrogen (d 15 N), the authors found all three species to be primarily herbivorous, feeding on both benthic and planktonic food sources, and overlapping substantially in diet.…”
Section: Invasive Tilapias In East Africa-interactions Between Invasive and Native Speciesmentioning
confidence: 99%